Social Organizations and Political Institutions: Why China and Europe Diverged - Joel Mokyr; Guido Tabellini (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper discusses the historical and social origins of the bifurcation in the political institutions of China and Western Europe. An important factor, recognized in the literature, is that China centralized state institutions very early on, while Europe remained politically fragmented for much longer. These initial differences, however, were amplified by the different social organizations (clans in China, corporate structures in Europe) that spread in these two societies at the turn of the first millennium AD. State institutions interacted with these organizations, and were shaped and influenced by this interaction. The paper discusses the many ways in which corporations contributed to the emergence of representative institutions and gave prominence to the rule of law in the early stages of state formation in Europe, and how specific features of lineage organizations contributed to the consolidation of the Imperial regime in China.
Keywords: 330